PENGARUH MEDIA VIDEO TUTORIAL TERHADAP HASIL BELAJAR MENGGAMBAR BENTUK DALAM PELAJARAN SENI RUPA DI SMP NEGERI 3 PADANG - Sinta Widiana Putri, Dra. Zubaidah, M.Pd., Drs. Eswendi, M.Pd. (Universitas Negeri Padang, 2017)
The purpose of this study is to determine the effect of video tutorial media on the result of learning to draw a form in art lesson in SMP Negeri 3 Padang. This study uses a quantitative type of experimental research with the determination of samples using purposive random sample technique to grade VII students in SMP Negeri 3 Padang. The sample in this research is class VII.1 as the experimental class and class VII.2 as the control class. Data collection is done through the instrument of learning result test (action test). Data analysis techniques performed are normality test, homogentas test, and hypothesis testing phase. The conclusion of the research that video tutorial media has a significant influence on the result of learning to draw a from in art lesson in SMP Negeri 3 Padang.Keywords: Media Video Tutorials, Student Learning Results